Sarcoidosis presenting as complete heart block in a 45-year-old farmer: an aetiology not to miss. (January 2014) - Riddington, Tom; Phan, Thanh T; Minns, Marissa; Turley, Andrew
Sarcoidosis should always be part of the differential diagnosis when faced with a young patient with significant cardiac conduction disease.